Quality assessment of discharge summaries from an emergency department in eastern Nepal - Giri, Rajani; Bhandari, R; Poudel, M; Gupta, P P (Health Renaissance, 2017)
Background: Discharge summaries are intended to transfer important clinical information from inpatient to outpatient settings and between hospital admissions. A good discharge summary helps physician to provide continuity of care which will in turn improve patient outcomes. Despite the importance of the discharge summary, there has been relatively little research in this area in Nepal. We therefore decided to review discharge summaries of patients discharged from emergency department in eastern Nepal. Objective: To assess the completeness of discharge summaries from emergency department. Methods: A total of 360 discharge summaries, representing 20% of discharge from the emergency department of B.P. Koirala Institute of Health Sciences, Nepal were randomly selected and evaluated. Quality of discharge for completeness was evaluated using recommendations by Joint Commission on Accreditation of Hospital for the presence or absence of the following key items: admission diagnosis, drug allergy, physical examination, significant laboratory test and results, discharge diagnosis, procedures, discharge medication (including dose and duration), follow up and attending physician signature. Results: The proportion of discharge summaries missing particular component of vital data ranged from less than 4% (no discharge medications) to 97% (no mention of drug allergy). Information was missing on patients discharge condition (74%), hospital course (61%), discharge instruction (57%) and the discharge diagnosis in (13%). Most of the discharge summaries were partially structured representing 75%. Ease of access to the diagnosis was 78%. Conclusions: Though most of the discharge summaries were structured and access to the diagnosis was 78%, considerable deficiencies in the completeness of discharge summaries were found. Health Renaissance 2015;13 (3): 41-47